Artificial intelligence and the law: cybercrime and criminal liability - Baker, Dennis J.; Robinson, Paul H. (Routledge, Taylor & Francis Group, 2021)
Emerging technologies and the criminal law / Dennis J. Baker and Paul H. Robinson -- Financial technology : opportunities and challenges to law and regulation / the Right Hon. Lord Hodge P.C. -- Between prevention and enforcement : the role of 'disruption' in confronting cybercrime / Jonathan Clough -- Preventive cybercrime and cybercrime by omission in China / He Ronggong and Jinglijia -- Criminal law protection of virtual property / Zhang Mingkai and Wang Wenjing -- Criminalising cybercrime facilitation by omission and its remote harm form in China / Liang Genlin and Dennis J. Baker -- Rethinking personal data protection in the criminal law of China / Lao Dongyan -- Using conspiracy and complicity for criminalising cyber-fraud in China : lessons from the common law / Li lifeng, Tianhong Zhao and Dennis J. Baker -- Sadie Creese -- AI v IP : criminal liability for intellectual property offences of artificial intelligence entities / Gabriel Hallevy -- Do not panic : artificial intelligence and criminal law 101 / Mark Dsouza.